USE OF ANTIBIOTICS IN THE PRESERVATION OF PRAWN - SURENDRAN, P K; IYER, K MAHADEVA (Fishery Technology, 2025)
Effect of incorporating chlorotetracycline (CTC) in ice upto 5 ppm level on the keeping quality of prawns has been studied. A shelf life extension by nearly six days is obtained for the CTC-iced sample over the control. The headless prawns absorbed greater amounts of CTC than whole prawns during storage in. CTC-ice. Traces of the antibiotic are found in the muscle of the CTC-iced prawns even after cooking for one hour. The cause of destruction of CTC when used for prawn preservation is discussed.